Echocardiographic Assessment of Patient with Ischemic versus non-ischemic Dilated Cardiomyopathy - Haque, Mostashirul; Arzu, Jahanara; Ahmed, Chaudhury Meshkat; Chowdhury, MSI Tipu; Singha, Chayan Kumar; Kabir, Faisal Ibn; Amin, Md Rasul; Mandal, Rayhan Masum; Khaled, Md Fakhrul Islam; Joarder, Ariful Islam; et al. (University Heart Journal, 2018)
Abstract not available University Heart Journal Vol. 13, No. 2, July 2017; 62-64